Pengaruh Kualitas Produk Terhadap Keputusan Membeli Melalui Kepuasan Pelanggan di Kawasan Kuliner Laksa Kota Tangerang, Provinsi Banten - Hendradewi, Savitri; Pramudito, Pramudito; Rachim, Faiza; Abduh, Mohammad Syaltut; Maulana, Alifatqul (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2026)
The development of traditional culinary businesses in Tangerang City has increased significantly along with the growing public interest in local specialty foods, including Betawi Laksa. In an increasingly competitive market, product quality is considered a crucial factor influencing customer satisfaction and purchasing decisions. This study aims to analyze the effect of product quality on purchasing decisions through customer satisfaction as an intervening variable. The research employed a quantitative approach using path analysis based on SmartPLS 4. A total of 250 respondents were selected through purposive sampling. Data were collected using a Likert scale questionnaire (1–5) and analyzed through validity and reliability tests, coefficient of determination (R²), as well as direct and indirect effect testing. The results indicate that product quality has a positive and significant effect on customer satisfaction and purchasing decisions. However, customer satisfaction does not have a significant effect on purchasing decisions and does not mediate the relationship between product quality and purchasing decisions. These findings suggest that product quality is the primary determinant influencing consumers’ decisions to purchase Laksa. It is recommended that Laksa vendors maintain consistent taste quality and hygiene standards, while local government should strengthen product development support and promote traditional culinary tourism. Keywords: product quality, customer satisfaction, purchase decision